Design and Validation of the Empowerment Model for Heads of Centers at the University of Applied Science and Technology - Mirzaei, Zeinab; Shirzad Kebriya, Baharak; Shariatmadari, Mehdi; Kordestani, Fereshteh (International Journal of Education and Cognitive Sciences, 2025)
Purpose: The present study aimed to design and validate the empowerment model for heads of centers at the University of Applied Science and Technology.  Methods and Materials: This research followed a sequential mixed-methods approach with an exploratory orientation. The qualitative phase consisted of meta-synthesis and Delphi stages, while the quantitative phase adopted a descriptive approach with survey and correlational methods. In the qualitative phase, the meta-synthesis stage involved a review of theoretical foundations and relevant literature from national and international databases. In the Delphi stage, 13 experts were selected using purposive non-random sampling. In the quantitative phase, the statistical population included all heads of centers at the University of Applied Science and Technology in Iran, from which 216 respondents were selected using multi-stage cluster random sampling. Data collection in the qualitative phase included a systematic literature review for the meta-synthesis stage and worksheets for the Delphi stage. In the quantitative phase, a researcher-developed questionnaire with 136 items, derived from the qualitative phase, was used to assess internal validity, while a 34-item questionnaire was employed to evaluate the validity of the model. The validity and reliability of research instruments were examined in both qualitative and quantitative phases, with results indicating that the tools were valid and reliable. Data analysis in the qualitative phase included systematic analysis in the meta-synthesis stage and Kendall's coefficient of concordance in the Delphi stage. In the quantitative phase, data analysis encompassed descriptive and inferential statistics, including confirmatory factor analysis and one-sample t-test, using Maxqda-V2018, SPSS-V23, and Smart PLS-V3 software. Findings: Findings revealed that the empowerment model for heads of centers at the University of Applied Science and Technology comprised the following dimensions: managerial competencies (18 indicators), communication skills (24 indicators), professional competencies (23 indicators), personal competencies (20 indicators), educational quality improvement (16 indicators), organizational learning (13 indicators), organizational effectiveness (10 indicators), and job satisfaction (12 indicators). Finally, based on the identified dimensions, components, and indicators, the research model was developed and assessed for internal and external validity, with results confirming its suitability. Conclusion: This study developed a comprehensive empowerment model for university heads, emphasizing managerial, communication, professional, and personal competencies, with validated internal and external reliability, contributing to improved leadership, organizational effectiveness, and educational quality.